A cross-sectional study of women's autonomy and modern contraception use in Zambia - Abigail Mangimela-Mulundano; Kirsten I. Black; Kate Cheney (BMC, 2022)
Abstract Background Modern contraceptive use effectively prevents unwanted pregnancies, promoting maternal and child health and improving the socio-economic well-being of women and their families. Women's autonomy has been shown to increase the uptake of modern contraception use. This research aimed to investigate the relationship between measures of women's autonomy and modern contraception use among partnered women in Zambia. Methods This cross-sectional survey study used data from the health census, the 2018 Zambia Demographic Health Survey. We measured women's autonomy using three indices: women's participation in decision-making, women's attitude towards wife-beating and women's household status. Information from 6727 women in a relationship, not pregnant, not planning pregnancy and aged between 15 and 49 years old were analyzed using descriptive statistics and adjusted odds ratios (AOR). Results The mean age of respondents was 32 years. Most women lived in rural areas (65%), and 81% were protestant. Current modern contraception use among partnered women was 8.8%. Women's autonomy was significantly associated with modern contraception use. Women with moderate autonomy (AOR = 1.054, P value = 0.004, 95% CI 1.048-1.312) and high autonomy (AOR = 1.031, P value = 0.001, 95% CI 1.013-1.562) had higher odds of using modern contraception compared to those with low autonomy. Other factors related to modern contraception use included a higher level of education (AOR = 1.181, P value = 0.012, 95% CI 1.091-1.783), increased wealth index (AOR = 1.230, P value = 0.006, 95% CI 1.105-1.766) and age, 15-24 (AOR = 1.266, P value = 0.007, 95% CI 1.182-2.113,) and 25-34 (AOR = 1.163, P value = 0.002, 95% CI 1.052-1.273). Conclusion This study argues that increasing women's assertiveness to make independent decisions within the household is cardinal to enhancing the uptake of modern contraception in Zambia and other low-and-middle-income countries. Governments and other stakeholders must therefore consider rolling out programs to boost women's autonomy, which in turn would support gender equality and reproductive health.